Projection of passenger cars’ fuel demand and greenhouse gas emissions in Iran by 2050 - Amin Hassani (Elsevier, 2021)
Passenger cars (PCs) not only are a major contributor to greenhouse gas (GHG) emissions in Iran but also pose severe energy security challenges due to their dependence on gasoline. This study aimed to understand the future trends of the gasoline demand and GHG emissions from PCs in Iran and assess the effectiveness of mitigation policies. The data were collected from multiple sources and used to develop the survival rate function of PCs. The study used back-calculation to compensate for the short period of stock data availability. The use intensity of PCs was estimated based on the gasoline consumption statistics. Econometric models were developed to project the future PC stock and use intensity based on economic indicators. Projections indicate that the PC stock of Iran triples and reaches 64 million by 2050, which resulting in a 280% increase in the gasoline demand and GHG emissions under business-as-usual scenario. Results also show that increasing the efficiency of new cars by 25% can decrease both gasoline demand and GHG emissions by 13% in 2050. Increasing the market share of cars running on compressed natural gas (CNG) to 35% by 2050 will also cut gasoline consumption by 19.6% without remarkable effect on GHG emissions. The results of study demonstrate that integrating the efficiency improvements, reforming fuel pricing, promoting alternative fuels, and enhancing car retirement can reduce gasoline demand and GHG emissions by 49% and 28%, respectively in 2050 and save 290 billion liters of gasoline from 2017 to 2050. According to the findings of this study, efficiency improvement and accelerated fleet turnover are the two most effective policies to curb GHG emissions in a developing country such as Iran. However, addressing the energy security issues of Iran is not possible without extensive promotion of CNG as an alternative transportation fuel.